WASTE MANAGEMENT USING LEAN-GREEN APPROACH: A CASE STUDY IN A FURNITURE COMPANY - Wurjaningrum, Febriana; Bhaskoro, Begawan Hero (Jurnal Ekonomi dan Bisnis Airlangga, 2024)
Introduction: Wooden furniture is one of Indonesia's superior products, with a low-efficiency level. However, the wooden furniture industry is often associated with intense environmental degradation and high levels of waste. In anticipating waste, a green manufacturing model proposed is Lean-Green manufacturing. This current study aims to explore the implementation of the Lean-Green model in a furniture company's waste processing system and assess the effectiveness of Lean-Green implementation. Methods: The research methodology was qualitative with the Lean-Green scoring method implemented in the supply chain of Company S. Data were collected through interviews and field observations. Results: Company S had a low score, meaning that the interaction between the Lean and Green approaches in the waste processing of the supply chain was not optimal. The Lean-Green implementation in the wooden furniture industry was effective in evaluating waste processing in the supply chain. The research findings urge the initiatives to improve the understanding and implementation of the Lean-Green concept. Conclusion and suggestion: The evaluation of the Lean-Green implementation helps the company's manager improve the supply chain with sustainable measures.